DISCURSIVE GOVERNMENTAL AND MEDIA RESPONSE TO COVID-19: THE CASE OF SERBIA - JOVANOVIĆ, SRĐAN MLADENOV (Society Register, 2020)
Serbia’s government, led by Aleksandar Vučić, has in scholarship been classified as semi-authoritarian, using Marina Ottaway’s classification. Its media have also been described as being in heavy, biased support of the government. Scholarship has further revealed that the Vučić-led, post-2012 government, has thrown the country backwards in time, with corruption and affairs being the primary instance by which the regime can be described. Expectedly, the response of the government and the government-supporting media to the COVID-19 pandemic has been less than professional. The initial response included official government press conferences in which the novel coronavirus was deemed to be ’funny’ and that, in the middle of the pandemic explosion and increased deathrate in Italy, Serbia’s population was advised to go to Italy for ’shopping’. The media furthermore tried to pin the pandemic to Serbia’s opposition alleged attempts to topple the government via ’coronavirus propaganda’. This article proposes to tackle the government’s and their supporting media’s responses to COVID-19 in February/March 2019 from a Discourse Analytical perspective.